1992
DOI: 10.1139/m92-032
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of murine macrophage responses stimulated with influenza glycoproteins

Abstract: Previously it was reported that influenza virus stimulated, nonspecific resistance was largely due to its glycoproteins, hemagglutinin (HA) and neuraminidase (NA). The enhancement of natural killer cell activity was the intrinsic property of NA and HA. In the present study, the stimulatory effect of these glycoproteins on the murine peritoneal macrophages was studied. Electrophoretically purified glycoproteins, NA and HA, of influenza virus A/USSR/90/77 (H1N1) were administered intraperitoneally to C3H/HeN mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…They have a part in pulmonary tissue damage, hypoxia, and toxicosis due to their toxic properties; on the other hand, they can induce apoptosis in virus-infected cells, thus contributing to the decrease in the total viral load. In this way ROS offer the fi rst line of defense against infection, preceding the alternative defense mechanisms of the organism (Arora and Houde, 1992). The presented results together with our previous data (Murzakhmetova et al, 2008) show that infl uenza A/Aichi virus infection is accompanied with defi cits in antioxidant enzyme activities and an increase in ROS and lipid peroxidation (LPO) levels in the lungs, livers, and sera, which can be overcome through supplementation with antioxidants.…”
Section: Discussionsupporting
confidence: 62%
“…They have a part in pulmonary tissue damage, hypoxia, and toxicosis due to their toxic properties; on the other hand, they can induce apoptosis in virus-infected cells, thus contributing to the decrease in the total viral load. In this way ROS offer the fi rst line of defense against infection, preceding the alternative defense mechanisms of the organism (Arora and Houde, 1992). The presented results together with our previous data (Murzakhmetova et al, 2008) show that infl uenza A/Aichi virus infection is accompanied with defi cits in antioxidant enzyme activities and an increase in ROS and lipid peroxidation (LPO) levels in the lungs, livers, and sera, which can be overcome through supplementation with antioxidants.…”
Section: Discussionsupporting
confidence: 62%
“…It is conceivable that the combination of high levels of TNF expression and the inhibition of NF-B activation (inferred from upregulated Nfkbia expression) act synergistically to cause signifi- 54). Specifically, the generation of oxygen radicals has been shown to be an important aspect of influenza virus virulence and pathology (3,6,13,14,20,50,79). Accordingly, we have identified the up-regulation of several important genes involved in the production of and response to superoxide radicals in the lungs of mice infected with influenza viruses.…”
Section: Discussionmentioning
confidence: 99%
“…It was further shown that the IFN-inducing potential of a specific strain correlated with the NA activity. Houde and Arora showed that recombinant NA, but not HA, induced the production of IL-1 and TNF-␣ in murine peritoneal macrophages (9,104,105), and another study has shown that NA promotes the conversion of TGF-␤ from the latent to the active form to an extent sufficient to induce TGF-␤-dependent apoptosis (223). The exact mechanism through which NA induces cytokine expression remains obscure yet is very important, given the high immunostimulatory activity of this viral protein.…”
Section: Influenza Virusmentioning
confidence: 99%